Effect of a carbohydrate-electrolyte solution on fluid balance and performance at a thermoneutral environment in international-level fencers - Chryssanthopoulos, C.; Tsolakis, C.; Bottoms, L.; Toubekis, A.; Zacharogiannis, E.; Pafili, Z.; Maridaki, M. (The Journal of Strength and Conditioning Research, 2020)
The purpose of the study was to examine a possible effect of a carbohydrate-electrolyte (CHO-E) solution on fluid balance and performance in fencing at a thermoneutral environment. Sixteen fencers performed two 120-minute training sessions separated by 7-14 days under similar environmental conditions (temperature: 20.3° C and humidity: 45-47%). Each session consisted of 60-minute conditioning exercises followed by 10 bouts of 3 minutes against the same opponent with 3-minute interval between each bout. Participants ingested at regular intervals either a 6% CHO-E solution or an artificially sweetened water (PL) in a counterbalanced order. No difference was observed between conditions in the heart rate responses, perceived exertion, changes in plasma volume, urine specific gravity, number of bouts won or lost, or points for and against. Considerable variability was observed in body mass changes that revealed significant differences at the time level (i.e., pre- vs. post-exercise) (F1,15 = 9.31, p = 0.008, Eta2 = 0.38), whereas no difference was found between conditions (i.e., CHO-E vs. PL) (F1,15 = 0.43, p = 0.52, Eta2 = 0.03) and conditions × time interaction (F1,15 = 3.57, p = 0.078, Eta2 = 0.19). Fluid loss was not significantly different between conditions (p = 0.08, d = 0.47). The blood glucose level was higher (p < 0.01) after exercise in CHO-E, whereas the blood lactate level was similar between conditions. In conclusion, the CHO-E solution was as effective as the artificially sweetened water in terms of fluid balance and fencing performance at a thermoneutral environment. Because of large individual variability, fencers should monitor their fluid intake and body fluid loss in training and competition.